Pengaruh Aplikasi Alfhabet Kids Terhadap Kemampuan Mengenal Huruf Pada Anak Usia 5-6 Tahun di RA Al Fathonah Rantewringin - Mukarromah, Mashlakhatul (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Development in early childhood needs to be developed from childhood. Nowadays, language development also needs to be considered and taught from an early age. This letter introduction uses media that is appropriate to today's era, namely the Alphabet Kids application. The aim of this research is to determine whether there is an influence of the Alphabet Kids application on the ability to recognize letters in children aged 5-6 years at RA Al Fathonah Rantewringin. This research uses experimental research with one group pretest-posttest design. The research was conducted at RA Al Fathonah Rantewringin on children aged 5-6 years. The subjects of this research were the children of RA Al Fathonah Rantewringin with a total of 30 children, namely 16 girls and 14 boys. The data collection methods in this research are observation and documentation. The technical analysis in this research uses the Simple T test. The results of this study show that the ability to recognize letters in children aged 5-6 years increased after being given treatment. The results of data analysis showed that the average pre-test score was 21 and the average post-test score was 42. The results of the paired simple t-test showed sig (2-tailed) 0.000 < 0.05, which means there is an influence of the Alphabet Kids application on The ability to recognize letters in children aged 5-6 years at RA Al Fathonah Rantewringin, where the children improved after treatment